Clinical Impact and Cost-Effectiveness of Whole Exome Sequencing as a Diagnostic Tool: A Pediatric Center’s Experience - Valencia, C. Alexander; Husami, Ammar; Holle, Jennifer; Johnson, Judith A.; Qian, Yaping; Mathur, Abhinav; Wei, Chao; Indugula, Subba Rao; Zou, Fanggeng; Meng, Haiying; Wang, Lijun; Li, Xia; et al. (Frontiers in Pediatrics, 2015)
Background: There are limited reports of the use of whole exome sequencing as a clinical diagnostic tool. Moreover, there are no reports addressing the cost burden associated with genetic tests performed prior to WES. Objective: We demonstrate the performance characteristics of WES in a pediatric setting by describing our patient cohort, calculating the diagnostic yield, and detailing the patients for whom clinical management was altered. Moreover, we examined the potential cost-effectiveness of WES by examining the cost burden of diagnostic workups. Methods: To determine the clinical utility of our hospital’s clinical WES, we performed a retrospective review of the first 40 cases. We utilized dual bioinformatics analyses pipelines based on commercially available software and in-house tools. Results: Of the first 40 clinical cases, we identified genetic defects in twelve (30%) patients, of which, 47% of the mutations were previously unreported in the literature. Among the 12 patients with positive findings, 7 have autosomal dominant disease and 5 have autosomal recessive disease. Ninety percent of the cohort opted to receive secondary findings, and of those, secondary medical actionable results were returned in three cases. Among these positive cases there are a number of novel mutations that are being reported here. The diagnostic workup included a significant number of genetic tests with microarray and single gene sequencing being the most popular tests. Significantly, genetic diagnosis from WES led to altered patient medical management in positive cases. Conclusions: We demonstrate the clinical utility of WES by establishing the clinical diagnostic rate and its impact on medical management in a large pediatric center. The cost-effectiveness of WES was demonstrated by ending the diagnostic odyssey in positive cases. Also, in some cases it may be most cost-effective to directly perform WES. WES provides a unique glimpse into the complexity of genetic disorders.